Cytomegalovirus-induced chronic intestinal pseudo-obstruction in an immunocompetent host - Chonmaitree, Piyanant; Soodcharoen, Asawin; Poonyam, Piyakorn; Laoarphasuwong, Nutthawut; Burivong, Wanaporn; Trongwongsa, Therdkiat; Raveesunthornkiet, Manasanan (Journal of Medicine and Health Sciences, 2025)
Chronic intestinal pseudo-obstruction (CIPO) is an uncommon presentation of cytomegalovirus (CMV) colitis. We present a case with CIPO caused by CMV in an immunocompetent host. A 45-year-old woman presented with chronic constipation and abdominal distension. A plain abdominal X-ray showed colonic dilatation, while a CT scan demonstrated circumferential wall thickening at the hepatic flexure of the colon and marked dilatation of the transverse colon. Colonoscopy revealed circumferential ulcers at the hepatic flexure and transverse colon, with pathology confirming positive immunostaining for CMV. The patient showed clinical improvement after treatment with ganciclovir and prucalopride. Secondary causes, including CMV infection, should be investigated in cases of CIPO. Dysmotility caused by CMV may represent the essential pathophysiology.